Bis[N-benzyl-2-(quinolin-8-yloxy)acetamide] monohydrate - Wang, Ming-Shi (International Union of Crystallography, 2011)
In the title compound, 2C(18)H(16)N(2)O(2)·H(2)O, the dihedral angles between the quinoline rings and the benzene rings in the two independent acetamide molecules are 80.09 (5) and 61.23 (5)°. The crystal packing is stablized by O—H⋯N and N—H⋯O hydrogen bonds between the acetamide and water molecules.